2009
DOI: 10.24839/1089-4136.jn14.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adult Disapproval of Cartoon Violence on Children's Aggressive Play

Abstract: Print ed in the USA. Pe ri od i cals postage paid at Chat ta noo ga, TN, and additional mailing offices. Statements of fact or opinion are the re spon si bil i ty of the authors alone and do not imply an opin ion on the part of the officers or mem bers of Psi Chi. Psi Chi does not accept paid advertising for its publications Eye on Psi Chi or Psi Chi Journal of Undergraduate Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 122 publications
(212 reference statements)
0
1
0
Order By: Relevance
“…In another facet of social learning theory, if an individual witnesses an act of aggression, that individual will be more likely to imitate that act of aggression later, especially if the act is successful in achieving the desired effect (Bandura, 1973). To illustrate, Miranda, McCluskey, Silber, von Pohle, and Bainum (2009) examined how play would be affected after a child viewed a 5minute clip of a violent cartoon in the presence of a silent adult or an adult who vocally disapproved of the violence within the cartoon. They found that children with the silent adult present demonstrated more aggres sive play and more verbal and physical aggression than children with the vocal adult.…”
Section: Resultsmentioning
confidence: 99%
“…In another facet of social learning theory, if an individual witnesses an act of aggression, that individual will be more likely to imitate that act of aggression later, especially if the act is successful in achieving the desired effect (Bandura, 1973). To illustrate, Miranda, McCluskey, Silber, von Pohle, and Bainum (2009) examined how play would be affected after a child viewed a 5minute clip of a violent cartoon in the presence of a silent adult or an adult who vocally disapproved of the violence within the cartoon. They found that children with the silent adult present demonstrated more aggres sive play and more verbal and physical aggression than children with the vocal adult.…”
Section: Resultsmentioning
confidence: 99%